Exploration of a novel class of HO-1 inducers as potential therapeutics for inflammatory disease - Fitzgerald, Hannah (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Autoimmune and inflammatory diseases such as rheumatoid arthritis (RA), multiple sclerosis (MS), psoriasis, and inflammatory bowel disease (IBD) are characterised by excessive and uncontrolled inflammation. Most of these diseases are incurable and their aetiology is only partially understood. Many patients become refractory to currently available treatments or show no response to these treatments from the outset. Given the increased incidence of these diseases, there is a growing need for novel anti-inflammatory therapies, with increased long-term efficacy and less adverse side effects. It is well known that many pathogens, including parasites, suppress host immune responses to establish latency and/or maintain persistent infection. Therefore, there has been increased interest in recent years in exploiting parasite-derived products for therapeutic benefit to treat autoimmune/inflammatory conditions. The extracellular parasite and causative agent of African sleeping sickness, Trypanosoma brucei (T. brucei), has evolved a number of strategies to avoid immune detection in the host. One recently described mechanism involves the conversion of host-derived amino acids to aromatic ketoacids, which are detected at relatively high concentrations in the bloodstream of infected individuals. These ketoacids have been shown to directly suppress inflammatory responses in murine immune cells, as well as acting as potent inducers of the stress response enzyme, heme oxygenase 1 (HO-1). Indeed, induction of HO-1 is considered a promising therapy for autoimmune and inflammatory conditions, and several studies have demonstrated that the HO reaction products, biliverdin and bilirubin, have potent anti-inflammatory, as well as antioxidant, properties. Administration of synthetic forms of these tetrapyrroles, or indeed upregulation of the inducible form of HO-1 following administration of cobalt protoporphyrin (CoPP), has been shown to alleviate inflammation in several animal models of disease. There is now a growing body of evidence supporting modulation of the HO-1 system as a treatment for gastrointestinal diseases, however, clinical implementation of HO-1 based therapies faces numerous challenges. Traditional HO-1 inducers primarily include metalloporphyrins, which strongly upregulate HO-1 expression, but are also associated with significant toxicity concerns and, while they have shown considerable efficacy in colitis models, are unsuitable for clinical use. Therapeutic administration of linear tetrapyrroles also faces challenges, therefore there is a solid rationale to identify safer and better tolerated alternatives to currently available HO-1 inducers. The aim of this study was therefore to investigate the immunomodulatory properties of T. brucei-derived ketoacids in primary human immune cells and further examine their potential as HO-1 inducers and novel therapies for inflammatory diseases, with specific focus on IBD. Results from this study demonstrate that the T. brucei-derived ketoacids, indole pyruvate (IP) and hydroxyphenylpyruvate (HPP), induce HO-1 expression through Nrf2 activation in human dendritic cells (DC). They also limit DC maturation, reduce the expression of co-stimulatory markers and suppress the production of pro-inflammatory cytokines, which, in turn, leads to a reduced capacity to differentiate adaptive CD4+ T cells. Furthermore, the ketoacids are capable of modulating DC cellular metabolism, inhibiting glycolysis and reducing expression of the key glycolytic enzyme, hexokinase 2 (HK2), as well as modulating expression of autophagy-related proteins. Finally, it is demonstrated that T. brucei-derived ketoacids are capable of inhibiting proliferation and pro-inflammatory cytokine production in T cells isolated from patients with IBD. This study therefore not only provides further evidence of the immune-evasion mechanisms employed by T. brucei, but also supports further exploration of this new class of HO-1 inducers as potential therapeutics for the treatment of inflammatory conditions.
APPROVED
Keywords: Trypanosoma brucei; Inflammatory Bowel Disease; HO-1/Nrf2; Anti-inflammatory therapy; Dendritic cells